2020
DOI: 10.3390/cells9081839
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Molecular DNA Methylation-Based Biomarkers through Genome-Wide Analysis of Response Patterns to BCG for Bladder Cancer

Abstract: Background: Bacillus Calmette-Guérin (BCG) immunotherapy, the standard adjuvant intravesical therapy for some intermediate and most high-risk non-muscle invasive bladder cancers (NMIBCs), suffers from a heterogenous response rate. Molecular markers to help guide responses are scarce and currently not used in the clinical setting. Methods: To identify novel biomarkers and pathways involved in response to BCG immunotherapy, we performed a genome-wide DNA methylation analysis of NMIBCs before BCG therapy. Genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It is of great guiding significance for the selection of treatment options and clinical decision support of patients with high-risk NMIBC to identify predictive biomarkers related to the BCG response and subsequent recurrence time (Kamat et al, 2018;Ilijazi et al, 2020;Shiota et al, 2020). Currently, most studies have focused on biomarkers in biological specimens, such as peripheral blood, urine, and tumor tissue from surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of great guiding significance for the selection of treatment options and clinical decision support of patients with high-risk NMIBC to identify predictive biomarkers related to the BCG response and subsequent recurrence time (Kamat et al, 2018;Ilijazi et al, 2020;Shiota et al, 2020). Currently, most studies have focused on biomarkers in biological specimens, such as peripheral blood, urine, and tumor tissue from surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In our application of NMF to radiomic features, the parts were the components of a reduced representation of the original hidden features, which may enable the recovery of biologically similar phenotypes. Considering that the molecular mode of BCG actions remains partially understood, NMF components might be a hint for potential pathways for BCG treatment failure based on previous reports about the cellular geography associated with the poor response to BCG (Ilijazi et al, 2020;Shiota et al, 2020;Tran et al, 2020). Compared with CT, the superiority of MRI has been documented with respect to the diagnostic performance and evaluation of treatment response of BCa, but there have been no studies on their performance in radiomics analysis (Wong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The authors further demonstrated that a targeted NGS-based methylation-based multi-cancer early detection test using a machine-learning classifier can simultaneously detect more than 50 cancer types with a single, fixed, low false positive rate of less than 1%, and can accurately localize the tissue of origin. Whereas the majority of DNA-methylation biomarkers have been described in the context of (early) cancer diagnosis there are also examples for DNA-methylation based therapy response markers [202,203]. Technologies typically applied for genome-wide and targeted DNA methylation analysis comprise DNA microarrays (e.g.,: Illumina EPIC bead array), NGS and quantitative PCR (qPCR).…”
Section: Future Direction Of Research In Dna Methylation Biomarkers F...mentioning
confidence: 99%
“…54 Subsequently, another genome-wide methylation analysis was performed on a cohort of high-risk NMIBC patients, concluding that the presence DNA methylation independently predicted 1-year clinical outcomes. 55 Ilijazi et al 56 found that gene promoter GPR158, when hypermethylated, was found to be the ideal predictor of BCG failure with an AUC value of 0.809 (P < 0.001). However, most of the methylation studies have modest sample sizes and varied definitions of threshold methylation differences, hence DNA methylation remains to be established as a reliable biomarker for BCG responsiveness.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Ilijazi et al 56 . found that gene promoter GPR158, when hypermethylated, was found to be the ideal predictor of BCG failure with an AUC value of 0.809 ( P < 0.001).…”
Section: Predictors Of Bcg Response and Failurementioning
confidence: 99%